Sleep Assessment in Competitive Athletes: Development and Validation of French Versions of the Athens Insomnia Scale and the Athlete Sleep Behavior Questionnaire - Baize, Diane; Meriaux-Scoffier, Stéphanie; Chrétien, Aurélia; Hayotte, Meggy; Piponnier, Enzo; d'Arripe-Longueville, Fabienne (Sleep Science, 2023)
Objective The purpose of this study was to develop and validate French versions of two questionnaires assessing competitive athletes' sleep: the Athens Insomnia Scale (AIS-FR) and the Athlete Sleep Behavior Questionnaire (ASBQ-FR).Methods Four complementary studies were carried out, with a total sample of 296 French competitive athletes from different sports and expertise levels. The studies aimed to develop preliminary versions of the AIS-FR and the ASBQ-FR (study 1), and then to examine their respective dimensionality and reliability (study 2), temporal stability (study 3), and concurrent validity (study 4). The dimensionality was established using confirmatory factor analysis. Similar and correlated psychological factor scales were used to examine the concurrent validity (the Insomnia Severity Index, the Pittsburgh Sleep Quality Index, the State-Trait Anxiety Inventory and the Positive and Negative Affect Schedule).Results The AIS-FR consists of eight items with two subfactors: nocturnal symptoms and diurnal symptoms, assessed by a uniformized 4-point Likert-type scale. The ASBQ-FR is composed of 15 items with three subfactors, which differs from the original English version: behaviors affecting sleep, behaviors related to anxiety, and sleep disturbances. Due to the Covid context and curfews, three items of the original scale were excluded from the statistical analyses because non-applicable. Both scales presented satisfactory psychometric properties.Discussion The AIS-FR and ASBQ-FR appear to be valid and reliable tools that can be used with competitive athletes for everyday training and research purposes. An ASBQ-FR version that includes the three excluded items should undergo validation testing once pandemic restrictions are eased.
Keywords: Surveys and Questionnaires; Sleep Initiation and Maintenance Disorders; Sleep Hygiene; Sleep; Sports; Athletes